2013
DOI: 10.1080/03630242.2013.796305
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Breast and Cervical Cancer Information for Hmong Women and Men

Abstract: Despite low breast and cervical cancer screening levels among Hmong women in the U.S. reported in the literature, understanding of the barriers to screening for Hmong women is limited. Health literacy issues may influence screening behavior for this population. This qualitative study explored sources of information about breast and cervical cancer including screening and identified barriers to seeking such information for Hmong women and men. We conducted semi-structured, in-depth interviews with 84 Hmong wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…A range of barriers to ethnic minority communities were identified in these articles, including distrust of the medical system among African American (Allen et al 2007, Wray et al 2009) and Chinese (Gao et al 2009) participants, misconceptions about the purpose of screening tests among Barbadian women, (Christian and Guell 2015), a lack of knowledge about national healthcare systems and screening (Arevian et al 2011, Erwin et al 2010, Kawar 2009, Team et al 2013, Thorburn et al 2013, Wangari Ngugi et al 2012) and cultural and religious traditions (Lee et al 2012, Wallace et al 2014. Researchers emphasised the role of socioeconomic factors in preventing access to screening and preventive measures such as HPV vaccination (Patel et al 2012, Paz-Soldan et al 2012, Schoenberg et al 2010.…”
Section: Structural Inequalitiesmentioning
confidence: 99%
“…A range of barriers to ethnic minority communities were identified in these articles, including distrust of the medical system among African American (Allen et al 2007, Wray et al 2009) and Chinese (Gao et al 2009) participants, misconceptions about the purpose of screening tests among Barbadian women, (Christian and Guell 2015), a lack of knowledge about national healthcare systems and screening (Arevian et al 2011, Erwin et al 2010, Kawar 2009, Team et al 2013, Thorburn et al 2013, Wangari Ngugi et al 2012) and cultural and religious traditions (Lee et al 2012, Wallace et al 2014. Researchers emphasised the role of socioeconomic factors in preventing access to screening and preventive measures such as HPV vaccination (Patel et al 2012, Paz-Soldan et al 2012, Schoenberg et al 2010.…”
Section: Structural Inequalitiesmentioning
confidence: 99%
“…We then conducted content analysis of the transcripts using NVivo 8 (QSR International, Cambridge, MA). Details of our methods are described elsewhere (Kue, Zukoski, Keon, & Thorburn, 2014; Thorburn, Keon, & Kue, 2013; Thorburn, Kue, Keon, & Lo, 2012; Thorburn, Kue, Keon, & Zukoski, 2013). The study was approved by the Oregon State University Institutional Review Board.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…However, Tran et al and Thorburn et al, indicated that healthcare providers and the internet are the most frequently used sources of information about cervical cancer. 39,40 One of the limitations of our study was that the results could not be generalized to the entire population of northern Iran, because our sample was obtained from a major primary health care center that provides free health care services. There are private practices that were not included in our study.…”
Section: Discussionmentioning
confidence: 99%